Language Features of Kipchak Riddles in the Codex Cumanicus: A Comparative Study (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the phonetic, lexical, and syntactic features of Kipchak riddles preserved in the Codex Cumanicus, one of the earliest written records of Turkic oral traditions. By analyzing the linguistic structure of the riddles and comparing them with modern Turkic languages, the study reveals the continuity and transformation of Turkic linguistic and cultural traditions. The analysis highlights how phonetic devices such as alliteration and assonance, rich metaphorical vocabulary, and simple, rhythmic syntactic patterns contributed to the preservation of cultural knowledge and artistic expression. The findings demonstrate that many linguistic and thematic features of medieval Kipchak riddles remain visible in contemporary Turkic folklore, emphasizing the enduring role of riddles in maintaining cultural identity across centuries.